Harvesting Sugar From Nonflowering Plants: Implications of a Marked Sugar Bait on Honey Bee (Hymenoptera: Apidae) Whole Hive Health. Issue 4 (30th July 2018) - Kapaldo, N O; Carpenter, J W; Cohnstaedt, L W
Abstract: Honey bees ( Apis mellifera ) are effective foragers for floral and extra-floral sources of sugars and as a result may easily be exposed to toxicants in the environment, such as pesticides. Toxic sugar baits (TSB) or insecticide-laced baits are designed for insect vector management but may be a danger to foraging honey bees and their hives. During a mosquito movement study at a zoological institution, nonflowering foliage surrounding the zoo was marked with sugar solution dyed with over the counter food-coloring. Mosquitoes and other insects foraged on the marked sugar and were collected within the zoo. Additionally, four of six honey bee hives within the zoo had workers that also foraged the dyed sugar and consequently colored approximately 57 kg of honey within the hives. This observation identifies a possibility route of toxicant accumulation within the hives from TSB and possible exposure may have whole hive health implications not previously described on an individual bee level.